Regional incidence of and reconstructive management patterns in melanoma and nonmelanoma skin cancer of the head and neck: A 3-year analysis in the inpatient setting. Issue 3 (March 2020) - Egeler, Sabine A.; Huang, Anne; Johnson, Anna R.; Ibrahim, Ahmed; Bucknor, Alexandra; Peymani, Abbas; Mureau, Marc A.M.; Lin, Samuel J.
Summary: Introduction: Currently, there is limited literature on reconstructive trends for inpatient head and neck skin cancer. Rather, studies have focused primarily on patients treated on an outpatient basis. To gain a better understanding of the effect that reconstructive correction of complex skin cancer defects has on the healthcare system, we examined the existing incidence and reconstructive trends of head and neck melanoma and nonmelanoma skin cancer (NMSC) in the inpatient setting. Method: We performed the analysis of the Healthcare Cost and Utilization Project Nationwide Inpatient Sample Database (NIS) for the years 2012–2014 of the United States (US). Adults diagnosed with melanoma skin cancer or NMSC of the head and neck region were included. Patient characteristics, reconstructive modality, surgical specifics, and outcomes were retrieved. Trends with time for reconstruction techniques were analyzed. Results: In total, 41, 185 patients with a diagnosis of skin malignancy were identified, of whom 5, 480 (13.3%) underwent reconstruction. Most patients were white (90.0%), male (71.6%), and had a diagnosis of NMSC (79.2%). An increase in flap reconstruction ( p < 0.001) was observed. After population adjustment, the highest incidence of skin malignancy was found in the Northeast. Conclusion: There has been a trending increase in inpatient NMSC and melanoma skin cancer of the head and neck region, correlating to an increase in the reconstructive procedures performed, and greater cost burden. Resources may be allocated toward early identification and treatment for skin cancer to help control the current rise in complex skin cancer cases necessitating inpatient admission.